2014
DOI: 10.1016/j.virol.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serpin A5 levels in the cervicovaginal fluid of HIV-1 exposed seronegatives suggest that a subtle balance between serine proteases and their inhibitors may determine susceptibility to HIV-1 infection

Abstract: HIV-exposed seronegative individuals (HESNs) are persons who remain seronegative despite repeated exposure to HIV, suggesting an in vivo resistance mechanism to HIV. Elucidation of endogenous factors responsible for this phenomenon may aid in the development of new classes of microbicides and therapeutics. We compared cervicovaginal protein abundance profiles between high-risk HESN and two control groups: low-risk HESN and HIV-positives. Four iTRAQ-based quantitative experiments were performed using samples cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 98 publications
3
24
1
Order By: Relevance
“…These protease inhibitors include 22 members of the serpin superfamily and two serine protease inhibitor Kazal type (SPINK) members, known to inhibit various serine proteases such as members of the kallikrein‐related peptidase family. The clinical importance of understanding protease activity in CVF was recently highlighted, as it was shown that resistance to HIV in CVF is dependent on the balance between serine proteases and serine protease inhibitors …”
Section: Resultssupporting
confidence: 80%
“…These protease inhibitors include 22 members of the serpin superfamily and two serine protease inhibitor Kazal type (SPINK) members, known to inhibit various serine proteases such as members of the kallikrein‐related peptidase family. The clinical importance of understanding protease activity in CVF was recently highlighted, as it was shown that resistance to HIV in CVF is dependent on the balance between serine proteases and serine protease inhibitors …”
Section: Resultssupporting
confidence: 80%
“…The proteomic analysis of vaginal fluid can provide more information about the pathophysiological conditions affecting the female genital tract [118,119]. 63 potential biomarkers for pregnancyrelated problems such as intra-amniotic inflammation [112,120] and preterm labour/preeclampsia [121][122][123][124][125], cervical cancer [126] and HIV infection [127] were identified (Table 6) using quantitative proteomics techniques and six biomarkers were validated.…”
Section: Cervicovaginal Fluid As Source For Biomarkers For Obstetricsmentioning
confidence: 99%
“…An iTRAQ based study was conducted to analyze CFV from HIV-exposed seronegative individuals (HESN) that were at high risk compared to low risk (HESN) and HIV positive patients. The research revealed that Serpin A5 was up regulated and Myeloblastin was downregulated in high risk HESN when compared to that in the other groups [66]. Further study into the mechanism behind HIV resistance and development of treatments is recommended [66].…”
Section: Cervicovaginal Fluidmentioning
confidence: 99%
“…The research revealed that Serpin A5 was up regulated and Myeloblastin was downregulated in high risk HESN when compared to that in the other groups [66]. Further study into the mechanism behind HIV resistance and development of treatments is recommended [66]. …”
Section: Cervicovaginal Fluidmentioning
confidence: 99%